2019
DOI: 10.3390/su11236558
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Indoor Analysis: A Holistic Approach to Understand the Relation of Higher Education Classrooms and Academic Performance

Abstract: The influence of learning space on users has been broadly accepted and tested. However, the literature has focused on single factor research, instead of holistic approaches. Additionally, lower educational levels have been the focus of interest, while higher education is moving towards multi-method teaching. This paper focuses on how learning spaces for different purposes (practice and lecture rooms) may influence academic performance from a holistic approach of learning physical environment perception. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…It has been shown that the adaptation of iPEP for the measurement of student perception of the variables of the physical learning space in Primary Education is valid and reliable. Likewise, the study has allowed us to investigate the factorial structure of the learning space construct, resulting in an organization in three factors: Workspace comfort, natural environment and building environment, which support previous results [25]. However, findings have evidenced that more question would be needed in order to improve the percentage of learning space measure in primary education level.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It has been shown that the adaptation of iPEP for the measurement of student perception of the variables of the physical learning space in Primary Education is valid and reliable. Likewise, the study has allowed us to investigate the factorial structure of the learning space construct, resulting in an organization in three factors: Workspace comfort, natural environment and building environment, which support previous results [25]. However, findings have evidenced that more question would be needed in order to improve the percentage of learning space measure in primary education level.…”
Section: Discussionsupporting
confidence: 78%
“…First, the design of the questionnaire was adapted to the cognitive level of primary school students based on the Indoor Physical Environment Perception scale (iPEP scale) [25,37] (focused on university students), previously based on the holistic model of Barret, Davies, Zhang and Barret [38]. Next, public elementary schools are randomly chosen from the regions of A Coruña and Lugo (Galicia, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With us, only one discriminatory function can be specified, because we only have two groups of thermal comfort: g (good) or b (bad). In the case of two groups, discriminant analysis is analogous to multiple regression and is then called Fisher linear discriminant analysis (LDA) [32,33]. In the case of two groups, the linear equation is used as a discriminatory function:…”
Section: Linear Discriminant Analysis (Lda)mentioning
confidence: 99%